Unraveling Cuticle Formation, Structure, and Properties by Using Tomato Genetic Diversity - Petit, Johann; Bres, Cécile; Reynoud, Nicolas; Lahaye, Marc; Marion, Didier; Bakan, Bénédicte; Rothan, Christophe (Frontiers in Plant Science, 2021)
The tomato (Solanum lycopersicum) fruit has a thick, astomatous cuticle that has become a model for the study of cuticle formation, structure and properties in plants. Tomato is also a major horticultural crop and a long-standing model for research in genetics, fruit development and disease resistance. As a result, a wealth of genetic resources and genomic tools have been established, including collections of natural and artificially induced genetic diversity, introgression lines of genome fragments from wild relatives, high-quality genome sequences, phenotype and gene expression databases, and efficient methods for genetic transformation and editing of target genes. This mini-review reports the considerable progresses made in recent years in our understanding of cuticle by using and generating genetic diversity for cuticle-associated traits in tomato. These include the synthesis of the main cuticle components (cutin and waxes), their role in the structure and properties of the cuticle, their interaction with other cell wall polymers as well as the regulation of cuticle formation. It also addresses the opportunities offered by the untapped germplasm diversity available in tomato and the current strategies available to exploit them.